2015
DOI: 10.1007/s00405-015-3777-4
|View full text |Cite
|
Sign up to set email alerts
|

Voice quality and surgical detail in post-laryngectomy tracheoesophageal speakers

Abstract: The objective of this study is to assess surgical parameters correlating with voice quality after total laryngectomy (TL) by relating voice and speech outcomes of TL speakers to surgical details. Seventy-six tracheoesophageal patients' voice recordings of running speech and sustained vowel were assessed in terms of voice characteristics. Measurements were related to data retrieved from surgical reports and patient records. In standard TL (sTL), harmonics-to-noise ratio was more favorable after primary TL + pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Many studies consistently reported a different formant pattern between alaryngeal and laryngeal speakers [9,15,17,18,[22][23][24]. As the filtering properties of the vocal tract can be reflected by vowel formants, these findings tend to point to the hypothesis that the vocal tract configuration of alaryngeal and laryngeal speakers are different.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Many studies consistently reported a different formant pattern between alaryngeal and laryngeal speakers [9,15,17,18,[22][23][24]. As the filtering properties of the vocal tract can be reflected by vowel formants, these findings tend to point to the hypothesis that the vocal tract configuration of alaryngeal and laryngeal speakers are different.…”
Section: Discussionmentioning
confidence: 65%
“…Somewhat similar results were reported for Indian English and Dutch vowels. Maruthy et al [23] reported an increase only in F1 in Indian TE speakers, while Jacobi et al [24] found an increase only in F2 of Dutch TE speakers. Such findings are in line with the imaging studies of the vocal tract after laryngectomy using X-ray and magnetic resonance imaging (MRI) [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The voice quality and speech effort in patients with laryngectomy rehabilitated with esophageal voice are widely different. The tone of the pharyngoesophageal segment and the quality of the new sound source are based on the dynamics of adaptation and vibration of the pharyngeal mucosa (3) , varying according to the individual characteristics of this population (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Beslenme desteğinin etkili olabilmesi için ise operasyondan yaklaşık 7-15 gün önce ağız yoluyla, tüp ile veya damar yoluyla başlanması gerekmektedir. 29,30 Beslenme desteğinde bütün baş-boyun kanserli hastalar tedavi öncesi gıda alımı ve beden kitle indeksi açısından değerlendirilmeli, kilo kaybına dikkat edilmelidir. .…”
Section: Beslenme Desteği̇unclassified